BEST PRACTISE PENGEMBANGAN KURIKULUM DI SEKOLAH DASAR MELALUI EKSTRAKULIKULER PRAMUKA DI SD NEGERI KLITREN YOGYAKARTA : Indonesia - Vina Nathania; Dhiniaty Gularso (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe curriculum development through the Scout extracurricular program at SD Negeri Klitren Yogyakarta as a best practice in strengthening students’ character. The study employed a descriptive qualitative approach with a best practice method. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The results showed that the Scout extracurricular program was implemented systematically by applying curriculum development principles and experiential learning approaches. The program contributed positively to improving students’ discipline, responsibility, independence, leadership, cooperation skills, and environmental awareness, while supporting the implementation of the Merdeka Curriculum and the Pancasila Student Profile.